Efektivitas Sumber Daya Manusia Kesehatan Terhadap Pelayanan Kesehatan Masyarakat Di Puskesmas Babakan Kota Mataram Berdasarkan Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan - Rizqia, Dinda Ayu; Hamzah, Any Suryani (Fakultas Hukum Universitas Mataram, 2024)
The purpose of the study is to determine the effectiveness of health human resources in public health services at the Babakan Community Health Center, Mataram City based on Law Number 17 of 2023 concerning Health, and to determine the obstacle factors Health Human Resources from providing health services at the Babakan Community Health Center. The type of research is empirical legal research which analyzes the gap between what ought (das sollen) in Law Number 17 of 2023 concerning Health and the facts that occur in the field (das sein). Based on the result of the study, shows that The effectiveness of Health Human Resources in Public Health Services at the Babakan Community Health Center has not been effective, because the number of medical personnel and health workers is still insufficient, so there are often long queues of patients for treatment at the Babakan Community Health Center. Consequently, the Community Health Center often receives complaints from patients regarding the long queues for health services at the Babakan Community Health Center, the factors inhibiting the Effectiveness of Health Human Resources in Community Health Services at the Babakan Health Center, Mataram City Based on Law Number 17 of 2023 concerning Health general factors legal factors, service factors, community factors. Specific factors unequal distribution of health workers, slow service system.